2013
DOI: 10.1088/0004-637x/763/2/123
|View full text |Cite
|
Sign up to set email alerts
|

GOODS-HERSCHEL: SEPARATING HIGH-REDSHIFT ACTIVE GALACTIC NUCLEI AND STAR-FORMING GALAXIES USING INFRARED COLOR DIAGNOSTICS

Abstract: We have compiled a large sample of 151 high redshift (z = 0.5 − 4) galaxies selected at 24 µm (S 24 > 100 µJy) in the GOODS-N and ECDFS fields for which we have deep Spitzer IRS spectroscopy, allowing us to decompose the mid-infrared spectrum into contributions from star formation and activity in the galactic nuclei. In addition, we have a wealth of photometric data from Spitzer IRAC/MIPS and Herschel PACS/SPIRE. We explore how effective different infrared color combinations are at separating our mid-IR spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 43 publications
(54 reference statements)
5
74
0
Order By: Relevance
“…This selection criterion yields a contribution of 10 luminous AGN to our sub-sample of 167 24-µm-bright BCGs, with all but one lying within the 0.78 < z < 1.36 redshift range. We note, however, that these numbers reflect only luminous AGN, as the Donley et al (2012) criterion misses 39% of spectroscopically confirmed mid-infrared-bright AGN (Kirkpatrick et al 2013), i.e. low-luminosity and/or host-dominated AGN, and those with a strong 9.7-µm silicate absorption feature.…”
Section: Agn Versus Star-forming Contributionmentioning
confidence: 68%
“…This selection criterion yields a contribution of 10 luminous AGN to our sub-sample of 167 24-µm-bright BCGs, with all but one lying within the 0.78 < z < 1.36 redshift range. We note, however, that these numbers reflect only luminous AGN, as the Donley et al (2012) criterion misses 39% of spectroscopically confirmed mid-infrared-bright AGN (Kirkpatrick et al 2013), i.e. low-luminosity and/or host-dominated AGN, and those with a strong 9.7-µm silicate absorption feature.…”
Section: Agn Versus Star-forming Contributionmentioning
confidence: 68%
“…They determine an AGN fraction of just 9% at S 24 = 350µJy increasing up to 74±20% at S 24 ≈ 3 mJy. Also see Kirkpatrick et al (2013) for a detailed discussion of how AGN fraction changes with 24µm flux density limit.…”
Section: Mid-infrared Spitzer-selected Populationsmentioning
confidence: 99%
“…Donley et al (2012) redefined, in a more restricted way, the IRAC colours-based AGN selection criteria previously developed by Lacy et al (2004Lacy et al ( , 2007 obtaining a highly-reliable classification for deep IRAC surveys (referred to as the "Donley wedge" hereafter). Messias et al (2012) developed their own IR colour-colour diagram, using Ks and IRAC bands (the KI diagram) and, finally, Kirkpatrick et al (2012Kirkpatrick et al ( , 2013 presented two different combinations of colours that combine MIR and far-IR (FIR) photometry (Spitzer IRAC/MIPS and Herschel PACS/SPIRE) to classify high redshift (z = 0.5 − 4) galaxies selected at 24 µm with Spitzer IRS spectroscopy. These criteria will be briefly presented in the following.…”
Section: Agn Infrared Colour Diagnosticsmentioning
confidence: 99%
“…The line separate RE-AGN (above the line) from star-forming or passive galaxies (below the line), according to Kirkpatrick et al (2012Kirkpatrick et al ( , 2013 Bottom-Right: IR colour-colour plot showing log(S 8.0 /S 3.6 ) versus log(S 100 /S 24 ). The line separates RE-AGN (above the line) from star-forming or passive galaxies (below the line), according to Kirkpatrick et al (2012Kirkpatrick et al ( , 2013. In the two lower plots, empty symbols refer to 100 µm and 250 µm upper limits.…”
Section: Mir To Fir Photometrymentioning
confidence: 99%
See 1 more Smart Citation